Efectos del producto bruto interno per cápita y empleo formal en el acceso al crédito directo en la región Loreto 2012-2021 - Coelho Silva, Erick Willy (2023)
The objective of this research work is identify the level of general statistical significance of the effect of GDP per capita and level of formal employment on access to direct credit in the Loreto region 2012-2021. Its importance arose from the growing interest in bankarization issues and the lack of studies on the problem from the perspective of households that contribute to projecting regional financial development. The research was of a quantitative type, applied level and non-experimental design with longitudinal data. After applying the OLS regression for time series and pass the significance test at 90% confidence, it was concluded that by increasing the GDP per capita of the Loreto region by S/ 100, the percentage of the population of legal age with access to direct credit will increase by 0.078% in the following year; and by increasing the percentage of the employed economically active population with formal employment by 1%, the percentage of the population of legal age with access to direct credit will increase by 0.281%. In addition, the two variables together explain 82.06% of the behavior of the dependent variable.